RELASI KUASA AKTOR AGAMA DENGAN PEKERJA SEKS KOMERSIAL (PSK) PADA LOKALISASI GUNUNG SAMPAN - Rizal M, Muhammad Khoirul; -, Bandiyah; Mahaswari Jayanthi Mertha, Anak Agung Sagung Mirah (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2021)
This research was conducted in the localization of Gunung Sampan, Situbondo Regency, Situbondo Regency, by explaining the power relations of religious actors with CSWs and the State. The objectives of this study are: (1). Describe the religious humanist approach to CSW, (2). Knowing the role of religious actors in the failure of the State to overcome the problem of localization. The theory used is Louis Althusser's theory of the ideological apparatus and Abraham Maslow's theory of humanism and William Liddle's humanist approach to religion. This study is using descriptive qualitative methods to obtain data. The Outcomes of this study indicate a power relationship between religious actors and prostitutes through a religious humanist approach to form religious awareness. The presence of religious actors is an advantage for the Situbondo Regency Government which has failed to solve the problem of prostitution. Keywords: Power Relations, Religious Actors, CSWs, Gunung Sampan Localization